HEALTH TECHNOLOGY ASSESSMENT OF MEDICAL DEVICES IN EUROPE: PROCESSES, PRACTICES, AND METHODS. (27th September 2016) - Fuchs, Sabine; Olberg, Britta; Panteli, Dimitra; Busse, Reinhard
Abstract : Objectives: To review and compare current Health Technology Assessment (HTA) activities for medical devices (MDs) across European HTA institutions. Methods: A comprehensive approach was adopted to identify institutions involved in HTA in European countries. We systematically searched institutional Web sites and other online sources by using a structured tool to extract information on the role and link to decision making, structure, scope, process, methodological approach, and available HTA reports for each included institution. Results: Information was obtained from eighty-four institutions, forty-seven of which were analyzed. Fifty-four methodological documents from twenty-three agencies in eighteen countries were identified. Only five agencies had separate documents for the assessment of MDs. A few agencies made separate provisions for the assessment of MDs in their general methods. The amount of publicly available HTA reports on MDs varied by device category and agency remit. Conclusions: Despite growing consensus on their importance and international initiatives, such as the EUnetHTA Core Model ®, specific tools for the assessment of MDs are rarely developed and implemented at the national level. Separate additional signposts incorporated in existing general methods guides may be sufficient for the evaluation of MDs.